Fathers' Perceptions of Parenting Classes in Kindergarten - Diana Indah Palupi; Hamid Patilima (Journal of Childhood Development, 2024)
The family is the earliest and most important environment for a child because the family is regarded as the first policy for the child's education, and the primary responsibility for education lies with the family. The involvement of parents, especially fathers, in early childhood education is essential. Schools and parents need to work together to coordinate foster care. Parenting class is a type of activity that is carried out to integrate childcare and education in school and at home. But in reality, the rate of father attendance in the parenting class activities organized by the educational unit is still low. This research aims to determine the father's perception of parenting classes conducted in kindergarten. This research uses qualitative methods with a descriptive approach. Data collection techniques include interviews, observations, and documentation. The research conducted interviews with five male informants who had children in kindergarten. The results show that parenting class is a very useful activity because it can be one of the means for parents to add insight into childcare as well as harmonize parenting between home and school. The involvement of a father in childcare has a long-term positive impact on the growth and development of the child. However, the main obstacle is the low attendance rate of the fathers because parenting class activities are generally done during working hours. Besides, the activities that allow you to engage are in the form of racing or activities related to physical activity.